Organic Semiconductor/Polymer Blend Films for Organic Field‐Effect Transistors. Issue 9 (13th June 2019) - Riera‐Galindo, Sergi; Leonardi, Francesca; Pfattner, Raphael; Mas‐Torrent, Marta
Abstract: The development of low‐cost printed organic electronics entails the processing of active organic semiconductors (OSCs) through solution‐based techniques. However, the preparation of large‐area uniform and reproducible films based on OSC inks can be very challenging due to the low viscosity of their solutions, which causes dewetting problems, the low stability of OSC polymer solutions, or the difficulty in achieving appropriate crystal order. To circumvent this, a promising route is the use of blends of OSCs and insulating binding polymers. This approach typically gives rise to films with an enhanced crystallinity and organic field‐effect transistors (OFETs) with significantly improved device performance. Recent progress in the fabrication of OFETs based on OSC/binding polymer inks is reviewed, highlighting the main morphological and structural features that play a major role in determining the final electrical properties and some future perspectives. Undoubtedly, the use of these types of blends results in more reliable and reproducible devices that can be fabricated on large areas and at low cost and, thus, this methodology brings great expectations for the implementation of OSCs in real‐world applications. Abstract : Recent progress on the use of organic semiconductors blended with insulating binding polymers as active materials in organic transistors is overviewed. This route leads to more reliable, less expensive devices with enhanced electrical performance.